Look up! - Chong, Chin-ho, 1987-; Kim, My Hyun (New York : Holiday House, 2016)
When a girl in a wheelchair calls to people far below to look up and see her, one finds a way to brighten her day.
Keywords: People with disabilities -- Fiction; Neighborliness -- Fiction; Perspective (Philosophy) -- Fiction; Children with disabilities -- Juvenile fiction; Neighborliness -- Juvenile fiction; Tall buildings -- Juvenile fiction; Perspective (Philosophy) -- Juvenile fiction; Picture books for children; Neighborliness -- Fiction; People with disabilities -- Fiction